Aetiological Profile of Facial Nerve Palsy Seen in Nigerian Tertiary Hospital - Olajide, Gabriel Toye; Adegbiji, Waheed Atilade; Akinbade, Akinwale Olaleye; Olajuyin, Anthony Oyebanji; Olowoyo, Paul (International Journal of Innovative Research in Medical Science, 2020)
Background/Aim: Facial nerve palsy may cause facial asymmetry, functional and cosmetic impairment, and therefore imposes great psychological and social problems on the individual with the condition. The aim of this paper was to highlight the aetiological profile of facial nerve palsy (FNP) in two tertiary institutions in Ekiti, southwest, Nigeria. Methods: This was a retrospective review of patients with facial nerve palsy seen and treated at Ear, Nose & Throat (ENT) clinic. All folders and registers of patients diagnosed with facial nerve palsy from January 2010 to December 2019 in the central, ENT and Dental medical records departments were retrieved and reviewed. The information extracted included the socio-demographic characteristics of the patients, clinical presentation, type and aetiology of FNP, side affected, diagnosis/impression, nature of impairment, type of lesion, onset of the disease, treatment and outcome. Results: Of 76 patients analysed, 48(63.2%) were males and 28(36.8%) were females given a male to female ratio of 1:1.7. Their age ranged between 5 to 72 years with a mean of 39.83 ± 17.58 SD. The age range 21-40 years was most commonly affected, representing 31 (40.8%). The commonest cause of facial nerve paralysis was Bell’s palsy in 32(42.1%), followed by trauma 28(36.9%). Of the 28 (36.9%) that was caused by trauma, road traffic injury constituted 15(53.6%). Half (50.0 %) of the lesion affected right side of the face. Seventy (92.1%) was treated medically. Majority (37.0%) presented within one week of their symptoms. All the patients presented with deviation of mouth, followed by inability to close eye in 70 (92.1%). Higher proportion (88.2%) of our patients had lower motor neuron lesion. Conclusion: This study found that majority of our patients was young adults. Bell’s palsy was a major cause of facial nerve paralysis followed by trauma. Most of our patient presented early and did well on conservative treatment. High index of suspicion is essential especially when patients present with injuries involving head and neck region.